A Machine for Bubble Wrapping Glass Perfume Bottle - Fazail, Fadhilah Nurhanisah; Masood, Ibrahim (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The perfumes industry in Malaysia is forecasted to grow in 2023 and the cylindrical glass perfume bottle is overlapped with other items during delivery process due to high demand which makes the bottle fragile, crack and broken. So, the main objective of this study is to design a bubble wrapping machine for packaging cylindrical glass perfume bottle that limited to a cylindrical bottle with maximum 14 cm height and bubble wrap as the wrapper. The machine has been designed and simulated in SolidWorks software and then, the machine and manual worker has been compared in term of time of wrapping and process of wrapping. The machine has been designed with six sub-assemblies. As a result, the machine is faster in time of wrapping and have simple process in wrapping process.